2022
DOI: 10.1108/pr-02-2021-0091
|View full text |Cite
|
Sign up to set email alerts
|

A cross-industry comparison of how women leaders experience gender bias

Abstract: PurposeThis paper compares how women leaders in four US industries–higher education, faith-based non-profits, healthcare and law–experience 15 aspects of gender bias.Design/methodology/approachThis study used convergent mixed methods to collect data from 1,606 participants. It included quantitative assessment of a validated gender bias scale and qualitative content analysis of open-ended responses.FindingsResults suggest that, while gender bias is prevalent in all four industries, differences exist. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
1
7
1
Order By: Relevance
“…Men received higher compensation than women even in female-predominant fields, including family medicine and pediatrics. This finding is concordant with those from a study showing gender bias not just in male-dominated fields but also in gender-balanced and female-dominated fields …”
Section: Discussionsupporting
confidence: 86%
“…Men received higher compensation than women even in female-predominant fields, including family medicine and pediatrics. This finding is concordant with those from a study showing gender bias not just in male-dominated fields but also in gender-balanced and female-dominated fields …”
Section: Discussionsupporting
confidence: 86%
“…Previous work has shown that mothers in STEM disciplines perceive that they have to work harder than STEM and non-STEM fathers and mothers not in STEM disciplines, possibly because of the academic STEM's masculine work culture (Kmec, 2013). However, a recent study has shown that gender bias is still prevalent in gender-balanced and female-dominated industries, including higher education (Stephenson et al, 2022). Here, we did not observe an effect of the eld of knowledge on the extent parents perceived bias, nor on how mothers felt in their workplace overall.…”
Section: Discussioncontrasting
confidence: 79%
“…Previous work has shown that mothers in STEM disciplines perceive that they have to work harder than STEM and non-STEM fathers and mothers not in STEM disciplines, possibly because of the academic STEM’s masculine work culture (Kmec, 2013 ). However, a recent study has shown that gender bias is still prevalent in gender-balanced and female-dominated industries, including higher education (Stephenson et al, 2022 ( https://www.emerald.com/insight/search?q=Amber%20L.%20Stephenson )). Here, we did not observe an effect of the field of knowledge on the extent parents perceived bias, nor on how mothers felt in their workplace overall.…”
Section: Discussionmentioning
confidence: 99%